The structure of SETT-Net - Zdravkova, Katerina; Bothe, Klaus; Budimac, Zoran (IEEE, 2003)
SETT-Net is an international Web-based network designed to enable training and teaching of a joint software engineering course. It consists of a Centre Point at the Humboldt University in Berlin and four National Centres: in Bulgaria, Germany, Macedonia, and in Serbia and Montenegro. The network is free for all lecturers and students at the participating schools in the project. Parts of the contents are passwor d protected. This paper presents the network structure, and the contents of the main site and the national sites, as well as the first experience of its application.
Keywords: Distance Learning, International Multilingual Virtual Classroom Network, Software Engineering